A cognitive therapy program for hearing-impaired employees suffering from mental distress. (April 2015) - Williams, Katharine Cecilia; Falkum, Erik; Martinsen, Egil Wilhelm
Abstract: Objective: To develop a cognitive therapy program to reduce mental distress among hearing-impaired employees. Design: In a pilot study we measured the development of mental distress and avoidant coping among hearing-impaired employees. Levels of mental distress were assessed using the hospital anxiety and depression scale (HAD), and the extent of avoidance with conversation tactics checklist CONV(AVOID). The findings were compared with the development in a treatment as usual (TAU) sample. Study sample: Fifteen participants with an equal distribution of male and female participants (M = 49.2 years) took part. The majority had mild to moderate hearing impairment. Results: The program appeared to be feasible and the adherence was good. The mean depression score was identical at pre- and post-intervention in the intervention group, and increased from 2.9 (SD 2.1) to 3.1 (SD 2.0) in the TAU group. Symptoms of anxiety (p < 0.01, 95 % CI (.82, 3.98)) and avoidant communication (p < 0.05, 95% CI (.5, 4.61)) decreased significantly in the intervention group, while an opposite pattern was observed during the TAU program. Conclusions: The program showed promising results. However, the preliminary results should be further investigated in a randomized controlled trial using a larger sample.